2023
DOI: 10.1007/s40121-022-00752-3
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Alveolar–Arterial Oxygen Tension Difference and the Severity of COVID-19 in Patients

Abstract: Introduction Coronavirus disease 2019 (COVID-19) emerged as a global pandemic and resulted in a significantly high death toll. Therefore, there is an urgent need to find a potential biomarker related to the disease severity that can facilitate early-stage intervention. Methods In the present study, we collected 242 laboratory-confirmed COVID-19-infected patients. The patients were grouped according to the alveolar to arterial oxygen tension difference (P A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…A study by Pipitone et al (D(A-o)O 2 ) showed higher sensitivity (77.8% vs. 66.7%), a positive predictive value (94% vs. 91%), and similar specificity (94.4% vs. 95.5%) as compared to the P/F ratio [7]. In another study, the (D(A-o)O 2 ) gradient identified COVID-19 patients with severe events even after adjusting for age and cardiovascular disease, which are both the most prominent predictors of unfavorable outcomes [31]. Consequently, imaging scores were developed, i.e., CT severity score (CTSS), which quantifies lung disease in COVID-19 [32], in a recent trial by Nokiani et al CTSS performance in triage was much lower than in earlier reports, but it performed better for the prognostification of COVID-19 [32].…”
Section: Previous Prediction Scoresmentioning
confidence: 90%
“…A study by Pipitone et al (D(A-o)O 2 ) showed higher sensitivity (77.8% vs. 66.7%), a positive predictive value (94% vs. 91%), and similar specificity (94.4% vs. 95.5%) as compared to the P/F ratio [7]. In another study, the (D(A-o)O 2 ) gradient identified COVID-19 patients with severe events even after adjusting for age and cardiovascular disease, which are both the most prominent predictors of unfavorable outcomes [31]. Consequently, imaging scores were developed, i.e., CT severity score (CTSS), which quantifies lung disease in COVID-19 [32], in a recent trial by Nokiani et al CTSS performance in triage was much lower than in earlier reports, but it performed better for the prognostification of COVID-19 [32].…”
Section: Previous Prediction Scoresmentioning
confidence: 90%